Analisis keterampilan 4c (critical thinking and problem solving, communication, collaboration, creativity and innovation) dalam buku siswa kelas iv subtema aku dan cita-citaku - Suci Fathonah Wati; Jenny Indrastoeti Siti Poerwanti; Sularmi Sularmi (Didaktika Dwija Indria, 2022)
Abstract. This study intends to describe the outcomes of the 4C skills analysis. (Critical Thinking and Problem Solving, Communication, Collaboration, Creativity and Innovation) Subtheme I and my values in the fourth grade student's textbook. This study utilized a qualitative descriptive approach for its design. The utilized methodology is content analysis. Document analysis is used to gather information. The test for validity employs theoretical triangulation and boosts the persistence of observations. The technique for data analysis consisted of three steps: data reduction, data display, and verification. The results indicated that communication abilities were 100 %, with the majority of Let’s Reading activities focusing on communication. 76% of students scored above average in critical thinking and problem solving, Let's Practice tasks that emphasize critical thinking and problem solving, 37% of students were found to possess collaboration abilities, and Let's Discuss activities are the most effective at encouraging students to collaborate, 16% of youngsters demonstrated creative and imaginative abilities, and Let's practice and Collaborate with Parents activities are the most influential in fostering these qualities. Based on these data, it can be stated that the subtheme's activities incorporate 4C competencies..Kata kunci: The 4Cs, critical thinking and problem solving, communication, collaboration, creativity and innovation, Student book.